(untitled) (Research, Society and Development, 2020)
After introducing to the subject and detailed study of the tools, the articles proposed the creation of a model flowchart to assist in the performance of the managers in front of their collaborators. Using the exposed Bibliography, three tools of strategic management of people and their diverse unfolding were defined. By means of field research, the general flowchart was made and then the application of the same was determined. At the end, the results were analyzed and it was concluded that the proposed article was successful in achieving the double win.